Legal Challenges in the face of the Decisive Transformation of the Media: Is the Balance between Copyright and New Digital Business Models Possible, considering the Current Changing Landscape? - Cantalejo, Mireia Moreso (Law, State and Telecommunications Review, 2020)
Purpose ”“ Approach and analyze the technological industries in society, as a global society, and how it is approached from the legal point of view. This study aims to make an analysis of the social context and technological progress and determine what main legal problems arise. There is also the purpose of investigating what impact new technologies have had in the audiovisual industry globally, taking into account the emergence of new digital business models, in order to determine their legal nature. Methodology ”“ The methodology used is mainly based on the analysis of the different Laws that regulate the digital market. The approach has been directed at European claims to respond to new digital models and discover if the result has had an effective application on citizens. Findings ”“ The study sets out as objectives achieved cross-border access of audiovisual platforms in the European territorial area. Objective met in a positive way but still with many inconveniences. It is noted a clear advantage for users, but with universal challenges, such as the exploitation of audiovisual content within the Right to information. Practical Implications ”“ If the laws were more current, companies and technological industries could give a more effective response to society, while creating wealth. It also shows the comparison between a European system, more protectionist towards the user, for example, with the protection of personal data, with respect to the Latin American system law. These differences impact economically differently in each country. Originality ”“ The study detects the most fragile points, the current conflicts of the digital platforms and shows the lines to follow through public policies.